Pengaruh Pendidikan Kesehatan Tentang Diet Gout Terhadap Pengetahuan Penyakit Gout Athritis di Posyandu Lansia Bagas Waras Kartasura - Indrawati, Susi; , Arina Maliya, S.Kep., Ns.,M.Si., Med (2016)
Gout arthritis is a disease that attacks the joints due to abnormal purine metabolism. One of the prevention of gout is to avoid consuming foods high in purines such as offal foods, foods that have been preserved, goose meat. Elderly who suffer from gout athritis often have a relapse; this is the case because it deals with the knowledge and awareness related atrhritis gout sufferers. of the value - the value of health or health behaviors so that, still play an optimal role in the provision of health education. This study as a research plan Quasi Experiment using pre-test and post-test control group design. Collection date usid a questionnaire while the test data analysis using Independent sample t-test and paired sample t-test. The test results Independent sample t-test pre-test treatment group and control group (p-value = 0.112). Post-test treatment group and control group (p-value = 0.001). The test results pairet sample t-test pre-test and post-test control group (p-value = 0.770), while the pre-test and post-test (p-value = 0.001) treatment group. Conclusion of the study is the level of knowledge about the disease gout arthritis before health education about gout diet is largely lacking and pretty, the level of knowledge about the disease gout arthritis after health education about gout diet is largely good, while the elderly who do not receive health education is largely self and there are significant health education about gout diet to decrease the knowledge about the disease gout arthritis in elderly Posyandu elderly Bagas Kartasura Sane.